Anatolia is the beginning of Turkish carpet arts and graphics - Zaymoglu O. Займоглу О. (Рroblems of engineering and professional education, 2023)
The article examines the history of carpets that emerged in Central Asia, referring to the similarities and differences between carpets and the symbolic values of their designs. Turkish rugs exchanged traditions of carpets, materials and painting techniques, motifs and types of Central Asian-speaking Turkic countries. Most of the modern Antalya carpets are based on Ottoman carpet weaving techniques, such as Anatolian Seljuk, which are typical of Central Asian carpets. Despite some minor differences in their design, there are some similarities between the design of the Turkic states and communities where they are found in modern Anatolian carpets in terms of their symbolic meaning.